Understanding literacy development a global view - McKeough, Anne. (Mahwah, N.J. L. Erlbaum Associates, 2006)
"At a time when education is burdened by increasing economic pressure to do more with less, it is imperative that educators and decision makers at all levels have access to current, broad-ranging, and in-depth information and evidence to inform their choices. This volume, compiling critical research on a wide spectrum of literacy concerns, is an invaluable tool for scholars, teacher educators, professionals, and graduate students in the fields of literary education, early childhood education, educational psychology, educational policy, and related areas."--Book jacket.
Developing literacy: themes and issues / Anne McKeough and Marya Jarvey -- The child's route into literacy: a double-track journey / Ingvar Lundberg -- How to avoid reading failure: teach phonemic awareness / Tom Nicholson -- Teaching reading comprehension / Michael Pressley and Katie Hilden -- A cross-language perspective on learning to read / Richard C. Anderson and Wenling Li -- Struggling adolescent readers: a cultural construction / Donna E. Alvermann -- Family literacy in Canada: foundation to a literate society / Heather Sample Gosse and Linda M. Phillips -- Understanding the everyday: adult lives, literacies, and informal learning / Mary Hamilton -- Literacy and diversity: challenges of change / Seok Moi Ng -- Literacies within classrooms: whose and for what purpose? / Ileana Seda-Santana -- Lessons from the reading clinic / Michael W. Kibby and Debra A. Dechert.
Keywords: Reading -- Cross-cultural studies; Literacy -- Cross-cultural studies